Organic Blueberry Production in Florida - Doug Phillips; Peter Dittmar; Philip Harmon; Danielle Treadwell; Jeffrey Williamson; Oscar Liburd (EDIS, 2021)
There is a growing market in the United States and globally for fresh fruits and vegetables with reported health-enhancing properties. This includes blueberries, which are high in antioxidants and have been reported to improve heart health and contain anticancer properties. Fresh-market blueberry sales (conventional and organic) increased by 27% between 2013 and 2017, and that trend is expected to continue. In addition, there is an increasing level of consumer interest in organically grown produce (for environmental conservation, taste, and other perceived benefits), for which some consumers are willing to pay a premium over the price for a conventionally produced crop. This new 8-page publication of the UF/IFAS Horticultural Sciences Department discusses various aspects of organic blueberry production in Florida and is intended for use by those currently using or interested in pursuing organic production. Written by Douglas A. Phillips, Peter J. Dittmar, Philip F. Harmon, Oscar E. Liburd, Danielle D. Treadwell, and Jeffrey G. Williamson. https://edis.ifas.ufl.edu/hs1400